Mengintegrasikan Agama Islam Pada Anak ADHD; Studi Grounded Theory Pembentukan Karakter Islami Oleh Orang Tua Pasca Terapi Fungsi Eksekutif - Taufik Hidayat; Rahmah Rahmah; Fitriani Fitriani (Attractive : Innovative Education Journal, 2026)
Children with Attention-Deficit/Hyperactivity Disorder (ADHD) often exhibit maladaptive behaviors, including difficulties in peer relationships, noncompliance with rules, impulsive actions without considering consequences, and excessive hyperactivity. These challenges raise concerns regarding their future moral development, religious commitment, and social functioning as adults. This study aimed to develop a theoretical framework explaining the process of integrating Islamic values into the lives of children with ADHD following Executive Function (EF) therapy. A Grounded Theory design was employed involving ten parents of children with ADHD who had completed EF therapy at Ceria Kandangan Hospital. Data were collected through observations and in-depth interviews and analyzed using thematic analysis. The trustworthiness of the findings was ensured through credibility, dependability, and confirmability criteria. The findings revealed that the integration process was shaped by six core dimensions: parenting transformation, internalization of Islamic values in daily life, adaptive parental strategies, parental role modeling, synergy between EF therapy and religious practices, and the spiritual meaning attributed by parents to the parenting experience. The resulting Islamic character traits included regular prayer performance, supplication (dua), remembrance of God (dhikr), honesty, discipline, responsibility, moral awareness, understanding of reward and sin, self-control, obedience, emotional stability, and self-motivation. Furthermore, Uswah Hasanah (exemplary role modeling) emerged as the central mechanism facilitating both warm emotional attachment and the transmission of religious values, reflecting a form of spiritual parenting perceived by parents as an act of worship and a sacred trust (amanah).